Targeting exercise-related genes and placental growth factor for therapeutic development in head and neck squamous cell carcinoma - Shi, Qingyuan; Ying, Haiyue; Weng, Weibin (Frontiers in Pharmacology, 2024)
Background Human cancers, including head and neck squamous cell carcinoma (HNSCC), are complex and heterogeneous diseases driven by uncontrolled cell growth and proliferation. Post-translational modifications (PTMs) of proteins play a crucial role in cancer progression, making them a promising target for pharmacological intervention. This study aims to identify key exercise-related genes with prognostic value in HNSCC through comprehensive bioinformatics analysis, with a particular focus on the therapeutic potential of placental growth factor (PIGF). Methods Transcriptome data for HNSCC were obtained from The Cancer Genome Atlas (TCGA) database. differently expressed genes (DEGs) were identified and analyzed for their prognostic significance. Exercise-related gene sets were retrieved from the Gene Set Enrichment Analysis (GSEA) database. Functional enrichment analyses, including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and GSEA, were conducted. The biological functions and clinical implications of key genes were further explored through single-gene expression analysis, immune infiltration analysis, and in vitro cellular experiments. Results The study identified exercise-related genes associated with survival prognosis in HNSCC. GO and KEGG pathway analyses highlighted the biological functions of these genes, and Kaplan-Meier survival curves confirmed their prognostic value. PIGF expression analysis using TCGA data showed its diagnostic potential, with higher expression linked to advanced tumor stages. Single-cell sequencing revealed PIGF's role in the tumor microenvironment. In vitro experiments demonstrated that PIGF plays a pivotal role in enhancing cell proliferation and colony formation in HNSCC, with PIGF knockdown significantly impairing these functions, highlighting its importance in tumor growth regulation. Additionally, PIGF's predictive performance in drug sensitivity across cancer datasets suggests its potential as a pharmacological target, offering opportunities to modulate the immune microenvironment and improve therapeutic outcomes in cancer treatment. Conclusions This study provides new insights into the molecular mechanisms underlying HNSCC and identifies exercise-related genes, particularly PIGF, as promising biomarkers for clinical treatment and personalized medicine. By focusing on PTMs and their role in cancer progression, our findings suggest that targeting PIGF may offer innovative therapeutic strategies.